Оцінка нормативно-правового забезпечення п'яти прав медичних працівників в Україні = Assessment regulatory support five of medical workers in Ukraine - V. M. Mikhal'chuk (Kazimierz Wielki University, 2015)
Mikhal'chuk V. M. Оцінка нормативно-правового забезпечення п'яти прав медичних працівників в Україні = Assessment regulatory support five of medical workers in Ukraine. Journal of Education, Health and Sport. 2015;5(11):389-398. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.34178 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A389-398 https://pbn.nauka.gov.pl/works/671703 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 20.11.2015.   УДК 614.2:341[614.253.8]   ОЦІНКА нормативно-правового забезпечення п'яти прав медичних працівників в Україні ASSESSMENT Regulatory Support FIVE OF MEDICAL WORKERS IN UKRAINE   В. М. Михальчук V. M. Mikhal'chuk   Національна медична академія післядипломної освіти імені П. Л. Шупика Shupyk National Medical Academy of Postgraduate Education   Summary     The article presents the results of analysis of regulatory framework of the five rights of health professionals inUkrainein the spectrum of the three groups of legal documents: the Constitution, laws ofUkraineand regulations.     Keywords: legal and regulatory provision, the right to health care workers, Laws of Ukraine.  Резюме             В статті висвітлено результати аналізу нормативно-правового забезпечення п'яти прав медичних працівників в Україні у спектрі трьох груп нормативно-правових документів: Конституції України, Законів України та підзаконних актів. Ключові слова: нормативно-правове забезпечення, права медичних працівників, Закони України.   Резюме ОЦеНКА нормативно-правового обеспечения пяти прав медицинских работников в Украине. В статье изложены результаты анализа нормативно-правового обеспечения пяти прав медицинских работников в Украине в спектре трех групп нормативно-правовых документов: Конституции Украины, Законов Украины и подзаконных актов. Ключевые слова: нормативно-правовое обеспечение, права медицинских работников, Законы Украины.